2023
DOI: 10.2147/ijn.s393507
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional, Highly Biocompatible, and Double-Triggering Caramelized Nanotheranostic System Loaded with Fe3O4 and DOX for Combined Chemo-Photothermal Therapy and Real-Time Magnetic Resonance Imaging Monitoring of Triple Negative Breast Cancer

Abstract: Purpose Owing to lack of specific molecular targets, the current clinical therapeutic strategy for triple negative breast cancer (TNBC) is still limited. In recent years, some nanosystems for malignancy treatment have received considerable attention. In this study, we prepared caramelized nanospheres (CNSs) loaded with doxorubicin (DOX) and Fe 3 O 4 to achieve the synergistic effect of combined therapy and real-time magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In terms of magnetic resonance properties, Fe 3 O 4 -Cy5.5-trastuzumab had a magnetization saturation intensity of 27.58 emg g −1 with negligible coercivity, but its T 2 relaxation rate still reached 42.29 mM −1 s −1 , and it also exhibited a clear trend of weakened imaging signals in vitro T 2 imaging, which indicated that nanoparticles connecting the monoclonal antibody and the fluorescent molecule did not significantly affect its performance in T 2 imaging [46,47]. In addition, combined with in vivo magnetic resonance imaging, Fe 3 O 4 -Cy5.5-trastuzumab nanoparticles showed a good targeting performance in magnetic resonance imaging [48][49][50][51].…”
Section: Discussionmentioning
confidence: 95%
“…In terms of magnetic resonance properties, Fe 3 O 4 -Cy5.5-trastuzumab had a magnetization saturation intensity of 27.58 emg g −1 with negligible coercivity, but its T 2 relaxation rate still reached 42.29 mM −1 s −1 , and it also exhibited a clear trend of weakened imaging signals in vitro T 2 imaging, which indicated that nanoparticles connecting the monoclonal antibody and the fluorescent molecule did not significantly affect its performance in T 2 imaging [46,47]. In addition, combined with in vivo magnetic resonance imaging, Fe 3 O 4 -Cy5.5-trastuzumab nanoparticles showed a good targeting performance in magnetic resonance imaging [48][49][50][51].…”
Section: Discussionmentioning
confidence: 95%
“…Hemolysis rates falling within the ranges of 0–2%, 2–5%, and 5–100% were categorized as non-hemolytic, mildly hemolytic, and hemolytic, respectively. 32 , 33 In this work, the hemolysis tests of the poly(HPMA)-Chl-PTA conjugate were processed and summarized in Figure S5 . PBS and pure water served as the positive and negative controls, which resulted in no hemolysis and significant hemolysis, respectively.…”
Section: Resultsmentioning
confidence: 99%